2017
DOI: 10.1038/srep46528
|View full text |Cite
|
Sign up to set email alerts
|

Compromised External Validity: Federally Produced Cannabis Does Not Reflect Legal Markets

Abstract: As the most widely used illicit drug worldwide, and as a source of numerous under-studied pharmacologically-active compounds, a precise understanding of variability in psychological and physiological effects of Cannabis varieties is essential. The National Institute on Drug Abuse (NIDA) is designated as the sole legal producer of Cannabis for use in US research studies. We sought to compare the chemical profiles of Cannabis varieties that are available to consumers in states that have state-legalized use versu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 46 publications
(77 reference statements)
7
76
0
Order By: Relevance
“…Our results clearly demonstrate that NIDA Cannabis samples are substantially different from most commercially available drug-type strains, sharing a genetic affinity with hemp samples in most analyses. Previous research has found that medical and recreational Cannabis from California, Colorado, and Washington differs significantly in cannabinoid levels from the research grade marijuana supplied by NIDA 14 Our genetic investigation adds to this previous research, indicating that the genetic makeup of NIDA Cannabis is also distinctive from commercially available medical and recreational Cannabis .…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Our results clearly demonstrate that NIDA Cannabis samples are substantially different from most commercially available drug-type strains, sharing a genetic affinity with hemp samples in most analyses. Previous research has found that medical and recreational Cannabis from California, Colorado, and Washington differs significantly in cannabinoid levels from the research grade marijuana supplied by NIDA 14 Our genetic investigation adds to this previous research, indicating that the genetic makeup of NIDA Cannabis is also distinctive from commercially available medical and recreational Cannabis .…”
Section: Discussionsupporting
confidence: 57%
“…This finding reveals that research conducted with NIDA Cannabis may not be indicative of the effects that consumers are experiencing. Additionally, research has demonstrated that Cannabis distributed by NIDA has lower levels of the principal medicinal cannabinoids (THC and CBD) and higher levels of degradation byproducts of cannabinoids (cannabinol, CBN) 14 Taken together, these results demonstrate the need for there to be greater diversity of Cannabis available for medical research and that the genetic provenance of those samples to be established to fully understand the implications of results.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations